The British navy, economy and society in the Seven Years War - Buchet, Christian (Boydell Press, 2013)
This book shows how the increasing efficiency of the Victualling Board enabled the navy to take advantage of agricultural, commercial and financial advances in the British economy to supply its front line fighting forces. It also shows how long-standing debates between those who favoured a state-controlled system and those who argued for the greater flexibility afforded by commercial contracting were resolved by developing a system which expertly balanced the two approaches. The author goes beyond maritime history to discuss how naval supply provided a huge stimulus for British finance, agriculture.